(untitled) (Journal of Nepal Geological Society, 2024)
Water is an invaluable natural resource for all living organisms, but its quality can be degraded by numerous anthropogenic and geogenic activities. Such issues are especially severe in areas near mining and mineral processing industries. The objective of this study is to evaluate the suitability of drainage water for livestock, drinking, and irrigation purposes around the Barapukuria Coal Mine, Dinajpur, Bangladesh. For this purpose, ten representative water samples were collected from different places of the mine drainage water during the dry season and were analyzed for various geochemical parameters, including pH, TDS, EC, major cations (Na+, K+, Ca2+, Mg2+) and anions (Cl–, HCO3–, SO42–). These parameters can be used to evaluate whether the water met quality standards set by the EQS, WHO and Bangladesh standards. Ca2+>Na+>Mg2+>K+ and HCO3–>SO42–> Cl– are the primary cations and anions trends, where the dominating water type is Ca–Mg–HCO3. Statistical analysis shows a good correlation between the ions suggesting homogenous water quality, whereas principal component analysis indicates three factors contribute to 84.368% of the entire variation. The water quality index (WQI) reveals that the majority of water samples are of good quality. The Gibbs plot indicates all samples fall into the rock dominance groups. The analysis of irrigation quality parameters, including % Na, SAR, KI, RSBC, MH, TH, and PI, along with Wilcox, USSL, and Doneen diagrams, indicates that the drainage water tends to be of good quality. Regular monitoring of water quality is recommended from the mine area.